Теоретическое обоснование математической модели процесса каталитического превращения CO - Ведь, Елена Валерьевна (НТУ "ХПИ", 2015)
В работе предложена математическая модель химической кинетики поверхностной каталитической реакции. Математическая модель описывает реакцию доокисления монооксида углерода до диоксида углерода на платиновой поверхности катализатора. В приближении разделения кинетики на быстрые и медленные движения. Практическая ситуация, отвечающая изучаемой модели, состоит в том, что происходит дожигание монооксида углерода до диоксида углерода в выхлопах автомобильных двигателей для улучшения состояния атмосферы.

Practical situation, accounting for the studied model is that CO afterburning to CO2 takes place in automobile engine’s exhaust gases for atmospheric condition improvement. Initial gaseous mixture consist of nitrogen, oxygen and carbon monoxide while exit gases composed of nitrogen, carbon dioxide and oxygen. For change in mixture’s component, physico-mechanical properties of the mixture, which determines its hydrodynamic and thermal behavior, changes. This paper presents a three-level modelling approach to the catalytic carbon monoxide oxidation in a temperature range between 400 K-800 K. The first level involves the description of the chemical kinetics for the exothermic reactions on the catalyst surface. The second level models the thermal and hydrodynamic processes in the boundary diffusion layer between the catalyst surface and the reactive stream. Finally, the third modelling level focuses on the representation of the hydrodynamic and thermal properties for the bulk multi-component gas flow at various gas velocity and temperature ranges. The dynamic behaviour of the reactive system has been studied through simulated runs.
Theoretical substantion model of catalytic CO conversion process
Keywords: моделирование математическое; конверсия; монооксид углерода; диоксид углерода; катализ; доокисление; кинетика; mathematical model; conversion; carbon monoxide; catalyst